2011
DOI: 10.4081/oncol.2008.203
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs in the diagnosis, prognosis and treatment of cancer

Abstract: MicroRNAs (miRNAs) are small non-coding RNAs that regulate critical cell processes such as cell proliferation, apoptosis and differentiation by modulating gene expression. MiRNAs deregulation has been observed extensively in cancer. Elegant studies have demonstrated that miRNAs are involved in the initiation and progression of several malignancies. In this review we will address the role of miRNAs in the diagnosis and prognosis of cancer. The development of new drugs mimicking or blocking miRNAs will be discus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Global alterations in miRNA expression have been illustrated in a large number of malignancies 18 34 35. Some studies have reported the downregulation of miR-129-1 expression in GBM tumors11 28 but its function remains unknown 36.…”
Section: Discussionmentioning
confidence: 99%
“…Global alterations in miRNA expression have been illustrated in a large number of malignancies 18 34 35. Some studies have reported the downregulation of miR-129-1 expression in GBM tumors11 28 but its function remains unknown 36.…”
Section: Discussionmentioning
confidence: 99%